Observer-based finite-time output feedback control of heat equation with Neumann boundary condition. Issue 14 (September 2020) - Ghaderi, Najmeh; Keyanpour, Mohammad; Mojallali, Hamed
Highlights: Design of a finite-time observer and output feedback finite-time controller for a heat PDE system. Using only one boundary displacement measurement for design of observer-based finite-time output feedback. Estimation of the system state variables in a finite-time by the proposed observer with linear switching observer gains. Finite-time stabilization of the closed-loop system using the proposed linear switching output feedback control. Abstract: This paper is concerned with the problem of boundary observer-based finite-time output feedback control for a heat system with Neumann boundary condition and Dirichlet boundary actuator. In this system, it is endowed a single sensor at the left boundary and actuator at the right boundary. First, a backstepping finite-time observer is designed. Based on linear switching observer gains with state-dependent switching, the proposed observer estimates the system state variables in a finite-time only using one displacement boundary measurement. Then, an observer-based linear switching output feedback control with state-dependent switching is presented, which steers any solution of the output feedback closed-loop system to zero in a finite-time. Finally, the simulation results are provided to support the theoretical results.